Prolotherapy in the management of temporomandibular joint disorders (Bangladesh Journal of Medical Science, 2025)
Discomfort and dysfunction in the jaw joint and its surrounding tissues are hallmarks of a complex set of disorders known as temporomandibular disorders (TMD). A newer method for treating TMD is prolotherapy, which is a kind of regenerative injectable treatment. A proliferant fluid, often dextrose, is injected into the joint area to induce a localised inflammatory response. This reduces temporomandibular joint discomfort while also encouraging tissue healing. When alternative treatment options for temporomandibular disorders (TMDs) have failed, prolotherapy may be a lifesaver. The regenerative nature of prolotherapy aligns with the need for interventions that address the underlying causes of TMD, such as joint laxity and ligamentous instability. For a successful outcome of prolotherapy, there must be a proper selection of patients and identification of specific subtypes of TMD. This article provides an overview of the different temporomandibular disorders and the application of prolotherapy in these disorders, summarizes existing evidence and highlights the key findings.BJMS, Volume: 24. Supplementary Issue 2025, Page : 156-159